(untitled) (Medico Legal Update, 2021)
Introduction: The basic human right is the right to life, along with the issue of the right to die. Euthanasia, as the right to die, is an urgent problem, the solution of which takes place on the border of medical science and jurisprudence. The Aim: Analyze the international experience of social and legal regulation of euthanasia. Materials and Method: To achieve the set goal, research method such as a comparative law method, theoretical analysis, system-analytical method and a method of conclusions systematization were applied is not prohibited, but it is not legalized in Germany, Spain, France, Albania, Israel. Conclusions: Analyzing the current international experience of euthanasia legal regulation, it stands to mention that even with the prohibition of euthanasia, there are some gaps in the legislation, whichcreate the possibility of passive euthanasia legal use by means of terminating life sustaining measures. It is important to enshrine the rules clearly regulating euthanasia in international law, otherwise this issue will be latent, and in the countries where there are legal gaps, excessive use of euthanasia will take place.